IL-13 and TH2 cytokine exposure triggers matrix metalloproteinase 7–mediated Fas ligand cleavage from bronchial epithelial cells - Wadsworth, Samuel J.; Atsuta, Ryo; McIntyre, J. Oliver; Hackett, Tillie-Louise; Singhera, Gurpreet K.; Dorscheid, Delbert R. (Journal of allergy and clinical immunology, 2010)
Bronchial epithelial damage and activation likely contribute to the inflammatory and airway-remodeling events characteristic of severe asthma. Interaction of Fas receptor (CD95) with its ligand (FasL; CD95L) is an important mechanism of cell-mediated apoptosis. Bronchial epithelial FasL expression provides immune barrier protection from immune cell-mediated damage. Membrane FasL (mFasL) is a cleavage target of matrix metalloproteinases (MMPs). We investigated whether the asthmatic T(H)2 environment might influence disease processes by increasing airway epithelial MMP-mediated cleavage of mFasL into proinflammatory soluble FasL. We used human airway epithelial cell lines and primary cells to model the human airway epithelium in vitro. Airway tissue from healthy subjects and patients with severe asthma was used to investigate MMP expression patterns in diseased airways. We demonstrate that active MMP-7 is present in the ciliated epithelial cells of normal human airways. In patients with severe asthma, MMP-7 levels are increased in basal epithelial cells. Airway epithelial cell lines (1HAEo(-) and 16HBE14o(-)) in vitro express constitutively high levels of MMP-2 and MMP-9 but relatively low levels of MMP-7. T(H)2 cytokine (IL-4, IL-9, and IL-13) treatment of 1HAEo(-) cells increased MMP-7 mRNA and activity, triggered colocalization of intracellular MMP-7 with FasL, and caused mFasL cleavage with soluble FasL release. Small interfering RNA knockdown shows that cytokine-induced mFasL cleavage is dependent on MMP-7 activity. MMPs serve multiple beneficial roles in the lung. However, chronic disordered epithelial expression of MMP-7 in patients with asthma might increase mFasL cleavage and contribute to airway epithelial damage and inflammation.